Total quality management and information technology - Tweedie, R. L. (International journal of value-based management, 1989)
Total Quality Management is now well-established as a central method for improving the efficiency and competitive position of firms and organizations. Developed in a manufacturing environment, it has shown the same attributes in administrative and service industries. In this paper we examine the potential for use in the Information Technology sector. Little impact has been made by TQM in the IT industry. We use the famous 14 points of W. Edwards Deming to discuss the potential and the pitfalls awaiting such implementation. The particular nature of the industry means that the techniques are not transparently transportable, and we develop some initial ideas for using TQM in situations which are traditionally seen as “one-off” and not susceptible to process analysis and measurement. We illustrate the idea of designing in quality by focusing on software design for reduction of maintenance costs and also touch on the role of the IT sector in corporate TQM development.